1997
DOI: 10.1093/ajcn/66.4.874
|View full text |Cite
|
Sign up to set email alerts
|

Aging, physical activity, insulin-like growth factor I, and body composition in Guatemalan women

Abstract: Aging is associated with diminished secretion of growth hormone and the major endogenous mediator of growth hormone action, insulin-like growth factor I (IGF-I). Aging is also associated with decreased physical activity. Alterations in body composition characteristic of the aging process (increased fat mass and decreased lean body mass) may be related to the decline in anabolic effects of IGF-I with aging, decreased physical activity, or both. Guatemalan women often maintain a high level of physical activity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…This would be another indication that the growth factors are involved in pubertal growth. Our observations of the age-and gender-associated variation in levels of IGFs and IGFBP-3 were consistent with the findings in the literature (21,(25)(26)(27)(28)(29)(30)(31). However, there were few publications describing the normal reference ranges of IGFBP-2, IGFBP-6, and ALS (32)(33)(34).…”
Section: Discussionsupporting
confidence: 91%
“…This would be another indication that the growth factors are involved in pubertal growth. Our observations of the age-and gender-associated variation in levels of IGFs and IGFBP-3 were consistent with the findings in the literature (21,(25)(26)(27)(28)(29)(30)(31). However, there were few publications describing the normal reference ranges of IGFBP-2, IGFBP-6, and ALS (32)(33)(34).…”
Section: Discussionsupporting
confidence: 91%
“…This would be another indication that the growth factors are involved in pubertal growth. Our observations of the age-and gender-associated variation in levels of IGFs and IGFBP-3 were consistent with the findings in the literature (21,(25)(26)(27)(28)(29)(30)(31). However, there were few publications describing the normal reference ranges of IGFBP-2, IGFBP-6, and ALS (32)(33)(34).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies of PA and IGF-I have been inconsistent. Two randomized control trials and seven cross-sectional analyses identified no relationships between PA and either IGF-I or IGFBP-3 levels among premenopausal [30,45] or postmenopausal women [46][47][48][49] or among women in general [11,50,51]. However, only three of the cross-sectional studies above [11,30,47] included more than 400 subjects.…”
Section: Discussionmentioning
confidence: 99%